Two Cases with Normocomplementhemic Urticarial Vasculitis: The Other Reasons Should Be Determined - Onur Balcı; Sedat Işıkay; Celal Varan; Arda Mehmet Kılınç; Mehmet Almacıoğlu (Güncel Pediatri)
Urticaria is mainly a fast consisting, scabious, erythematous and swelling lesions of the skin. Acute urticaria usually occurs after having a medicine or food. On the other hand, in the chronic urticaria, the process is longer, more scabious, and the skin lesions are more dramatic. In urticarial vasculitis, the lesions exist longer than 24 hours with pain or swelter instead of itchiness. It can be distinguished from basic urticaria with the damage of the small vessels by histopathologically. Here we present two normocomplementhemic urticarial vasculitis cases.